Climaticpark-py - A python framework for the climatic simulation of vehicular parking lots - Hyacinthe-Marie Nshuti; Juan Morales-García; Andrés Muñoz; Pedro J. Navarro; Diego Alonso; Pedro Sanchez; Bárbara Álvarez; Fernando Terroso-Saenz (SoftwareX, 2025)
Private vehicles are the dominant mode of commuting worldwide, accounting for a significant share of energy use and CO2 emissions. Urban growth has led to the expansion of surface parking lots, where vehicles are often exposed to intense solar radiation, raising cabin temperatures above 60 °C and increasing air-conditioning energy demand. Installing sunshades can mitigate this issue, but their effective deployment requires detailed analysis. This paper presents climaticpark-py, a Python library that simulates parking lots considering geographic and ambient conditions along with mobility patterns, enabling evaluation of sunshade configurations to optimize thermal comfort and energy efficiency even before physical implementation. The present software intends to contribute to the United Nation’s sustainable goal Make cities and human settlements inclusive, safe, resilient and sustainable.